看我七十二变 ：韩寒多重变身的反收编策略 = Seventy-two faces : Hanhan’s strategies of counter-corporation - 陈宇昕 Tan, Yu Xin (2010)
韩寒自1998年获得由《萌芽》杂志举办的“首届新概念作文大赛”一等奖后，因休学事件在媒体上衍发成一个文化现象，被广泛讨论。韩寒拥有青少年次文化的叛逆特质，并在这一基础上发展出属于韩寒本身的次文化特质。他创造了许多生活风格，并适时地更易策略。在不同时空语境下，韩寒得心应手地变换身份来展开次文化对母文化的抵抗。在赫布迪奇（Dick Hebdige）的次文化理论中，次文化是一种短暂的群体，他们一旦被媒体曝光，一旦被商业化，就会慢慢被主流文化所收编，并且失去抵抗权威的重要特性。韩寒作为一个次文化现象却不断规避被主流文化所同化，他游离于多元的空间，自穿梭各种语境，同时变换抵抗策略，无限延长了韩寒次文化的寿命。 本文将分析韩寒于不同时空所选择的策略以及揭示韩寒次文化所要抵抗的对象。同时，展示韩寒次文化的多重变异性质对于维持次文化活力的重要意义。 Hanhan became a cultural topic ever since he requested to withdraw from his high school after he had won the first prize in the New Concept Writing Competition in 1998. Hanhan carries varies youngsters’ subcultural traits that he could create his own subcultural identities. In Dick Hebdige’s subcultural theories he stated subcultural group as a short-lived group that they would easily be embodied by the mainstream culture ever since media’s widely attentions and commercialization. Hanhan always aware of this fact and tried to avoid his subcultural identity be died out.